Omkring suspensionen af Niels Hemmingsen i 1576 - Glebe-Møller, Jens (Kirkehistoriske Samlinger, 2014)
Summary Niels Hemmingsen (1513-1600), professor of theology at the University of Copenhagen from 1553 till he was suspended in 1579, was an international renowned theologian but was also held in high esteem in Denmark, where apart from his functions as a university professor, he had many important functions to fulfil. However, from 1574 onwards he came under fire because of the supposedly Calvinistic tendencies in his many theological writings, especially regarding the Holy Supper. Pressure from abroad, instigated by the Saxonian Electorate and his wife, finally let the Danish king, Frederic II, to suspend him in 1579. But leading up to the suspension, the governing body of the University, »Konsistorium«, of which Niels Hemmingsen himself was of course a member, had many arduous discussions of whether he should be suspended because of his erroneous, i.e. Calvinistic or »Cryptocalvinistic «, views of of the Holy Supper. The present article examines the deliberations in »Konsistorium« from 1576 onwards as well as Hemmingsen’s own writings on the Holy Supper and his various answers to his accusers, some of them his old friends. The conclusion being that in the late 15th Century, the debate about the understanding of The Holy Supper was as much a political as a theological one – with Hemmingsen choosing the wrong side.